MULTIMEDIA LECTURE AS A COMPONENT OF EDUCATIONAL ENVIRONMENT OF HIGH SCHOOL (ON EXAMPLE TRAINING SPECIALISTS PUBLISHING AND PRINTING) - Svitlana Denisenko (Ìнформаційні технології в освіті, 2017)
The article examines the role of lectures in today's educational environment university. It described the visualization lecture, as a new form of lecture that meets the educational needs of today. Multimedia features of lectures as a form of lectures-visualizations are defined. The author defines the peculiarities of the multimedia lectures, its teaching advantages, arising potential of multimedia technologies. The article presents approaches to the development and use of multimedia lectures. Implementation of scenario multimedia lecture is described. The author described the basic principles of preparation and presentation of educational material at lessons and ways implemention of them. The author cites the experience of creating and using multimedia lectures during classes in the professional training of publishers and printing. It described the didactic advantages of multimedia lectures in teaching of specialized subjects. It presents some examples of multimedia lectures, which were used in the classroom. In the article the place of multimedia lectures in modern educational environment of the university are defined. Multimedia Lecture - is the component of the educational environment designed to provide conditions maximize student learning, support educational interest and learning motivation, orientation for future professional activities